Our children at risk - Weisberg, Roger; Klein, Daniel; Freifeld, Riva ([S.l.] : Public Policy Productions [production company] ; Kuala Lumpur : Visual Resources [distributor], 1991)
The program is divided into four segments, the first of which deals with prenatal care. In the second segment, on pediatric care. In the third segment of the film deals with focus in on nutrition. The the last segment of the documentary deals with family preservation
Award winning films and videos
Camera, Maryse Albert...[et al.] ; sound, Lisa Schnall...[et al.] ; graphics, Peter Good
Keywords: Child health services -- United States; Medical care